(untitled) (Communications in Computational Chemistry, 2025)
With the rapid development of A-D-A non-fullerene acceptors, organic solar cells (OSCs) have made significant progress. However, compared to inorganic and perovskite solar cells, the energy loss in OSCs remains relatively large. In this Perspective, we summarize our recent computational advances in elucidating the mechanisms of energy loss in OSCs at the molecular level. We highlight strategies to minimize voltage loss during charge generation, suppress triplet-channel recombination, and reduce non-radiative voltage loss by modulating both molecular and aggregation structures.